Risk factors for pregnancy related complications among urban slum and non-slum women in Bangladesh - Mirajul Islam; Nasrin Sultana (BMC, 2019)
Abstract Background Bangladesh is facing a higher maternal mortality and morbidity than many other developing countries in the world. The majority of these maternal deaths occur due to pregnancy related complications. Although health facilities in urban areas in Bangladesh are widely available, women living in underprivileged urban areas are least likely to receive the maternal health services and as a result, they face more pregnancy related complications. Unfortunately, there are only a few studies on complications during maternal and delivery period in these areas. We aim to investigate the factors responsible for pregnancy related complications in urban slum and non-slum areas. Methods Data from the Urban Health Survey (UHS), 2013 were analyzed applying mixed logistic regression model. The response variable was complications during pregnancy, during/after delivery at the last birth and the total sample size was 6137. The adjusted odds ratios (AORs) along with their 95% confidence intervals (CIs) were also calculated to compare the magnitude of different risk factors for the pregnancy related complications. Results Younger mothers (age < 18 years) at the birth of their children had 24% (OR = 1.24, 95% CI: 1.01, 1.54) more odds to experience complications during pregnancy/delivery or after delivery compared to older mothers aged 18 to 35 years. The increased risk of complications was found among primiparous women. Women living in urban slum areas had higher pregnancy related complications than women living elsewhere. Migrant mothers faced more complications than women-who were not migrants. Women had greater pregnancy related complications when they delivered boy child than girl child, presumably from an increased size of the baby and resultant birth obstruction, assisted delivery and post partum haemorrhage. Moreover, a wanted pregnancy had fewer significant complications during pregnancy/delivery or after delivery than an unwanted pregnancy. Conclusions The study associates early maternal age, primiparity, unwanted pregnancy, women living in slum areas, women migrating from other cities or non-urban areas and NGO membership with increased risk of pregnancy related complications among urban women in Bangladesh. It is likely that addressing these risk factors for complications to the policymakers may help to reduce the maternal mortality and morbidity in Bangladesh.